Overall survival at 5 years of follow-up in a phase III trial comparing ipilimumab 10 mg/kg with 3 mg/kg in patients with advanced melanoma. Issue 1 (4th June 2020) - Ascierto, Paolo Antonio; Del Vecchio, Michelle; Mackiewicz, Andrzej; Robert, Caroline; Chiarion-Sileni, Vanna; Arance, Ana; Lebbé, Céleste; Svane, Inge Marie; McNeil, Catriona; Rutkowski, Piotr; Loquai, Carmen; Mortier, Laurent; et al.
Abstract : Background: We have previously reported significantly longer overall survival (OS) with ipilimumab 10 mg/kg versus ipilimumab 3 mg/kg in patients with advanced melanoma, with higher incidences of adverse events (AEs) at 10 mg/kg. This follow-up analysis reports a 5-year update of OS and safety. Methods: This randomized, multicenter, double-blind, phase III trial included patients with untreated or previously treated unresectable stage III or IV melanoma. Patients were randomly assigned (1:1) to ipilimumab 10 mg/kg or 3 mg/kg every 3 weeks for 4 doses. The primary end point was OS. Results: At a minimum follow-up of 61 months, median OS was 15.7 months (95% CI 11.6 to 17.8) at 10 mg/kg and 11.5 months (95% CI 9.9 to 13.3) at 3 mg/kg (HR 0.84, 95% CI 0.71 to 0.99; p=0.04). In a subgroup analysis, median OS of patients with asymptomatic brain metastasis was 7.0 months (95% CI 4.0 to 12.8) in the 10 mg/kg group and 5.7 months (95% CI 4.2 to 7.0) in the 3 mg/kg group. In patients with wild-type or mutant BRAF tumors, median OS was 13.8 months (95% CI 10.2 to 17.0) and 33.2 months (95% CI 19.4 to 45.2) in the 10 mg/kg group, and 11.2 months (95% CI 9.2 to 13.8) and 19.7 months (95% CI 11.6 to 25.3) in the 3 mg/kg group, respectively. The incidence of grade 3/4 treatment-related AEs was 36% in the 10 mg/kg group vs 20% in the 3 mg/kg group, and deaths due to treatment-related AEs occurred in four (1%) and two patients (1%), respectively. Conclusions: This 61-month follow-up of a phase III trial showed sustained long-term survival in patients with advanced melanoma who started metastatic treatment with ipilimumab monotherapy, and confirmed the significant benefit for those who received ipilimumab 10 mg/kg vs 3 mg/kg. These results suggest the emergence of a plateau in the OS curve, consistent with previous ipilimumab studies. Trial registration number: NCT01515189 .